A Multimodal Speech-Gesture Training Intervention for Patients With Schizophrenia and Its Neural Underpinnings – the Study Protocol of a Randomized Controlled Pilot Trial - Riedl, Lydia; Nagels, Arne; Sammer, Gebhard; Straube, Benjamin (Frontiers in Psychiatry, 2020)
Dysfunctional social communication is one of the most stable characteristics in patients with schizophrenia that also affects quality of life. Interpreting abstract speech and integrating nonverbal modalities is particularly affected. Considering the impact of communication on social life but failure to treat communication dysfunctions with usual treatment, we will investigate the possibility to improve verbal and non-verbal communication in schizophrenia by applying a multimodal speech-gesture training (MSG training). Here we describe the newly developed MSG training program and the study design for the first clinical investigation. The intervention contains perceptive rating (match/mismatch of sentence and gesture) and memory tasks (n-back tasks), imitation and productive tasks (e.g., SG fluency – similar to verbal fluency where words are accompanied by gesture). In addition, we offer information about gesture as meta-learning element as well as homework for reasons of transfer to everyday life as part of every session. In the MSG training intervention, we offer eight sessions (60 minutes each) of training. The first pilot study is currently conducted as a single-center, randomized controlled trial of speech-gesture intervention versus wait-list control with a follow-up. Outcomes are measured through pre-post-fMRI and standardized psychological questionnaires comparing two subject groups (30 patients with schizophrenia and 30 healthy controls). Patients and healthy controls are randomized in two intervention groups (with 20 being in the wait-training group and 10 in the training-follow-up group). With our study design we will be able to demonstrate the beneficial effect of the MSG training intervention on behavioral and neural levels.